Parametric analysis on the effect of V-type rotor magnet geometry on the dynamic performance of PMSMs - Ali, Ahmed Jadaan; Ahmed, Ahmed Hashim; Yahya, Ahmed Saad; Saied, Basil Mohammed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
The research examines how different dimensions of V-type permanent magnet synchronous motor (PMSM) magnets influence the magnetic flux between the rotor and the stator system because matching these dimensions optimizes the magnetic flux for better torque production. As long as the magnet size stays within the right dimensions, it builds greater flux density, which leads to better torque output and better efficiency. Research confirms that flow barriers strengthen engine capabilities. The research applies parametric optimization to find the perfect magnet shapes while showing how they boost electric vehicle motors to meet their requirements. Our tests with finite element method (FEM) show how changing magnet dimensions affects performance. Researchers adjust magnetic measurements frequently until the optimal setup of 50 mm thick by 4.5 mm wide emerges. Their action boosts flux density, which improves motor torque and energy capacity. At these optimal dimensions, the engine achieved 95% efficiency with precise flow barrier adjustments that helped increase torque output while reducing unstable electricity output.